Impaired Control of Epstein–Barr Virus Infection in B-Cell Expansion with NF-κB and T-Cell Anergy Disease - Arjunaraja, Swadhinya; Angelus, Pamela; Su, Helen C.; Snow, Andrew L. (Frontiers in Immunology, 2018)
B cell Expansion with NF-κB and T cell Anergy (BENTA) disease is a B-cell specific lymphoproliferative disorder caused by germline gain-of-function mutations in CARD11. These mutations force the CARD11 scaffold into an open conformation capable of stimulating constitutive NF-κB activation in lymphocytes, without requiring antigen receptor engagement. Many BENTA patients also suffer from recurrent infections, with 7 out of 16 patients exhibiting chronic, low-grade Epstein-Barr virus (EBV) viremia. In this mini-review, we discuss EBV infection in the pathogenesis and clinical management of BENTA disease, and speculate on mechanisms that could explain inadequate control of viral infection in BENTA patients.